2021
DOI: 10.1002/cmtd.202100052
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry at the Solid‐Solid Interface; Selectivity and Activity in Mechanochemical Reactions on Surfaces

Abstract: This paper summarizes the concepts that underpin the way in which forces exerted on chemical systems can either accelerate their rates or induce reaction pathways that cannot be accessed thermally. This was first described in 1935 by Evans and Polanyi who showed how hydrostatic pressure could accelerate the rates of chemical reactions using a thermodynamic analysis of transition-state theory to demonstrate that the reaction rate increased exponentially with pressure, and depends on a socalled activation volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 111 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…25 Consequently, there do not yet exist widely adopted methods to measure the kinetics of mechanochemical reactions. Although evidence has shown that mechanochemical conditions alter reaction pathways, [26][27][28][29][30][31] the fundamental question of how force changes the primary mechanochemical reaction to alter the trajectory that a reaction follows along the energy landscape from reactants to products has not yet been resolved to the satisfaction of the mechanochemistry community. To address this, here we discuss how recent, tip-based experiments have been used to isolate the kinetics of primary covalent bond-forming (CBF) mechanochemical reactions on surfaces, and how these studies have provided insight into the unique role force has on the outcomes of mechanochemical reactions carried out in mills and extruders.…”
Section: Introductionmentioning
confidence: 99%
“…25 Consequently, there do not yet exist widely adopted methods to measure the kinetics of mechanochemical reactions. Although evidence has shown that mechanochemical conditions alter reaction pathways, [26][27][28][29][30][31] the fundamental question of how force changes the primary mechanochemical reaction to alter the trajectory that a reaction follows along the energy landscape from reactants to products has not yet been resolved to the satisfaction of the mechanochemistry community. To address this, here we discuss how recent, tip-based experiments have been used to isolate the kinetics of primary covalent bond-forming (CBF) mechanochemical reactions on surfaces, and how these studies have provided insight into the unique role force has on the outcomes of mechanochemical reactions carried out in mills and extruders.…”
Section: Introductionmentioning
confidence: 99%